Dislocation of the mandible in a 47 year old patient - Klaudia Brożyna; Jędrzej Tkaczyk; Tomasz Bąk; Jolanta Wojciechowicz; Anna Gawęda; Marcin Baran; Tomasz Tomaszewski (Kazimierz Wielki University, 2017)
Dislocation of mandible is relatively uncommon disorder of temporomandibular joints. Disorder can occur during extreme dilation of mouth such as yawing, during dental treatments or endoscopic examination. 47- year old patient was admitted to the Department of Maxillo-facial Surgery in case of bilateral mandible dislocation. In this case the reposition in general anaesthesia was performed but ended up with failure.